Fostering Self-Awareness in Early Childhood: Definitions, Mechanisms, and Educational Implications - Wen Ma; Wang Xiufang; Zhangbo (New Ideas Concerning Arts and Social Studies Vol. 2, 2025)
This section deals with the third feature of metacognition: the self-awareness of children. Five studies describe self-awareness as mental activity, metacognitive awareness, self-regulatory, and metacognitive knowledge. It can be constructed in a natural classroom setting for preschool-aged children, such as writing, speaking, and positive emotion growth.